Peran Badan Pengawas Pemilihan Umum Dalam Pencegahan Praktik Money Politics Pada Pemilihan Kepala Daerah 2024 Di Kabupaten Sinjai - Aidil; Luhur Prianto, Andi; Amiruddin, Iswadi (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the role of the Election Supervisory Agency (Bawaslu) in efforts to prevent the practice of money politics in the 2024 Regional Head Election (Pilkada) in Sinjai Regency. This study uses a qualitative descriptive research method with a case study approach, this study was conducted for approximately two months at the Secretariat of the Sinjai Regency Election Supervisory Agency. Data collection was carried out through observation, interviews, and documentation. The results of the study indicate that the Sinjai Regency Election Supervisory Agency (Bawaslu) has carried out its role and responsibilities well in the regional head election (Pilkada) process in Sinjai Regency. Based on the analysis of the four indicators, it was found that the Sinjai Regency Election Supervisory Agency (Bawaslu) always strives to carry out its duties and promises to prevent the practice of money politics and ensure that the election process continues to run effectively. This study underlines the importance of utilizing technology in increasing effectiveness and accountability in preventing the practice of money politics in the election process in Sinjai Regency.